New species and new records of Eriococcus (Hemiptera, Coccoidea, Eriococcidae) from South America - Foldi, Imre; Kozár, Ferenc (Zootaxa, 2007)
The adult females of five new species in the genus Eriococcus are described and illustrated: Eriococcus christopherus, E. longisetosus E. paranaensis, from Brazil, and E. maximus and E. venezuelaensis from Venezuela. In addition, the following are recorded for the first time: E. dubius (Cockerell), E. maximus and E. venezuelaensis from Brazil and Venezuela and E. rhadinothrix (Miller & González) from Brazil. The most widespread species was E. maximus, which was collected from Brazil, Paraguay and Venezuela. A taxonomic key is provided for the separation of the seven species studied.